Self-reinforcing glass ceilings - Carlos F. Avenancio-León; Alessio Piccolo; Leslie Sheng Shen (Federal Reserve Bank of Boston, 2024)
After the gender pay gap narrows, what labor choices do men and women make? Several factors contribute to the persistence of the pay gap, such as workplace flexibility, systemic discrimination, and career costs of family. We show that how the labor market responds to the narrowing of the gap is just as pivotal for understanding this persistence. When the gender pay gap declines in a specific sector, women are relatively more likely to seek jobs in that sector, while men readjust their search to less equitable sectors. These compositional effects decrease female participation in less equitable sectors, which typically offer higher wages, reinforcing gender stereotypes and social norms that contribute to the glass ceiling. Through these effects, the same forces that reduce the gender pay gap at the bottom of the pay distribution also contribute to the persistence of gender inequities at the top. This self-reinforcing cycle underscores the need for reforms that are cross-sectoral and comprehensive to effectively achieve meaningful reductions in gender inequities across the labor market.
Keywords: J16; J71; O16; 330; Gender pay gap; gender norms; gender sorting; bank deregulation